Semantic Analysis of the Expression of Bliss Throughout Romantic Context in Taylor Swift's Song Lover - Syahla Fatia Zahra; Otong Setiawan Djuharie (Sintaksis : Publikasi Para ahli Bahasa dan Sastra Inggris, 2025)
This research investigates the semantic expression of romantic bliss in Taylor Swift’s song “Lover,” emphasizing how language conveys emotional intimacy and idealized love. The study is based on Geoffrey Leech’s (1981) theory of meaning, focusing on three aspects: conceptual meaning, connotative meaning, and affective meaning. This study uses a descriptive qualitative method to analyze selected parts of the lyrics. The findings reveal that Swift expresses emotional connections and her ideal of love through metaphorical language and symbolic expressions. Lyrics such as "We could leave the Christmas lights up until January" and "You're my, my, my, my lover" highlight how ordinary events become important emblems of emotional connection and romantic harmony. According to the study, Taylor Swift's "Lover" is a useful tool for semantic investigation as well as a well-liked love song. By her choice of words, Swift creates a lyrical rendering of love that resonates with audiences, thereby emphasizing how language can effectively convey emotional experiences.